2002
DOI: 10.1007/s11325-002-0161-6
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a Positive Association Between Pulmonary Function and Wine Intake in a Population-Based Study

Abstract: While total alcohol intake was not related to lung function, wine intake showed a positive association with lung function. Although we cannot exclude residual confounding by healthier lifestyle in wine drinkers, differential effects of alcoholic beverages on lung health may exist.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Indeed, a previous study from the same TESAOD cohort that used baseline alcohol and lung function parameters found heavy drinking to be associated with respiratory symptoms, particularly in association with heavy smoking (Lebowitz, 1981). In contrast, studies that included subjects with varied levels of alcohol intake have provided different, and somewhat inconsistent, results with some showing no association of alcohol with lung function after accounting for smoking status (Cohen et al, 1980; Sparrow et al, 1983), others showing negative associations (Lange et al, 1988; Zureik et al, 1996), but the majority showing enhanced lung function among light to moderate drinkers (Root et al, 2014; Schunemann et al, 2002; Sisson et al, 2005; Siu et al, 2010; Tabak, Smit, Heederik, et al, 2001; Tabak, Smit, Rasanen, et al, 2001; Twisk et al, 1998). These inconsistencies may be related to large inter-study differences in alcohol intake, age distributions, study design, and heterogeneity in other relevant demographic, clinical, and behavioral factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, a previous study from the same TESAOD cohort that used baseline alcohol and lung function parameters found heavy drinking to be associated with respiratory symptoms, particularly in association with heavy smoking (Lebowitz, 1981). In contrast, studies that included subjects with varied levels of alcohol intake have provided different, and somewhat inconsistent, results with some showing no association of alcohol with lung function after accounting for smoking status (Cohen et al, 1980; Sparrow et al, 1983), others showing negative associations (Lange et al, 1988; Zureik et al, 1996), but the majority showing enhanced lung function among light to moderate drinkers (Root et al, 2014; Schunemann et al, 2002; Sisson et al, 2005; Siu et al, 2010; Tabak, Smit, Heederik, et al, 2001; Tabak, Smit, Rasanen, et al, 2001; Twisk et al, 1998). These inconsistencies may be related to large inter-study differences in alcohol intake, age distributions, study design, and heterogeneity in other relevant demographic, clinical, and behavioral factors.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have found that moderate alcohol intake is associated with increased lung function measures – particularly forced vital capacity (FVC) and forced expiratory volume in one second (FEV 1 ) – in the general population, but these findings have not always been consistent even after taking into account possible confounders like concomitant cigarette smoking (Cohen et al, 1980; Frantz, Wollmer, Dencker, Engstrom, & Nihlen, 2014; Garshick, Segal, Worobec, Salekin, & Miller, 1989; Lange et al, 1988; Root, Houser, Anderson, & Dawson, 2014; Schunemann et al, 2002; Sisson et al, 2005; Siu, Udaltsova, Iribarren, & Klatsky, 2010; Sparrow, Rosner, Cohen, & Weiss, 1983; Tabak, Smit, Heederik, Ocke, & Kromhout, 2001; Tabak, Smit, Rasanen, et al, 2001; Twisk, Staal, Brinkman, Kemper, & van Mechelen, 1998; Zureik, Liard, Kauffmann, Henry, & Neukirch, 1996). A possible explanation for these discrepancies is that the relation of alcohol intake to lung function is largely dependent on both the quantity and duration of alcohol consumption.…”
Section: Introductionmentioning
confidence: 99%
“…Our finding of a relationship between higher alcohol consumption and a slower decline in FEV 1 seems peculiar. Lange et al 42 found that the effect on FEV 1 decline by a high alcohol consumption (350 g per week or more) was equivalent to 15 g of tobacco daily, while Schünemann et al 43 found no correlation between total alcohol consumption and lung function decline, but on the other hand a positive relationship between wine drinking and change in FEV 1 , which is most likely due to confounding by a healthier lifestyle in wine drinkers. The mean weekly consumption in our cohort was around 130 g, and by that substantially lower than that in the cohort of Lange et al, 42 which may explain some of the differences in observations.…”
Section: Discussionmentioning
confidence: 99%
“…11 Based on biological considerations, moderate drinking could exhibit beneficial effects on CRF by increasing insulin sensitivity, anti-inflammatory effects, enhancing levels of high-density lipoprotein cholesterol and adiponectin, improving pulmonary function, and by lowering of fibrinogen and lower blood pressures. 3537 Several detrimental actions of alcohol might explain lower CRF among participants with high average alcohol intake, including suppressed fat oxidation leading to insulin resistance, hypertriglyceridaemia, and weight gain and adiposity; inhibition of the pulmonary immune response and airway epithelial permeability, and airway leakage; decrease amount of glucose and amino acids used by the skeletal muscles with decrease in energy supply; decreased muscle capillarity, lower glycogen utilization levels; lower fatty acids; lower liver glucose output; and ethanol-induced hypoglycaemia. 3840…”
Section: Discussionmentioning
confidence: 99%